Motivation for Maintaining Oral Health and Its Association with Gingivitis among Pregnant Women at Berbek Public Health Center - Luthfi Zainur Rohmah; Bambang Hadi Sugito; Siti Fitria Ulfah; Imam Sarwo Edi (International Journal of Advanced Health Science and Technology, 2025)
Gingivitis is one of the most common oral health problems encountered during pregnancy, largely influenced by hormonal changes that heighten gingival vascularization and inflammatory responses. Preliminary findings from the Berbek Public Health Center, Nganjuk, indicated a high prevalence of gingivitis among pregnant women, reflecting inadequate oral hygiene practices and limited awareness. This situation underscores the need to understand behavioral determinants, particularly motivation, that may influence oral health status during pregnancy. Therefore, this study aimed to analyze the association between pregnant women’s motivation to maintain oral health and the occurrence of gingivitis in the working area of Berbek Public Health Center in 2025. A descriptive-analytic study with a cross-sectional design was conducted involving 30 pregnant women selected through purposive sampling. Motivation levels were assessed using a validated Likert-scale questionnaire, while gingival status was examined using the Loe and Silness Gingival Index. Data were analyzed using Spearman’s correlation test to determine the relationship between motivation and gingival condition. The results revealed that 56.7% of respondents had moderate motivation and 43.3% had strong motivation for maintaining oral hygiene. Gingivitis assessment showed that 60% of participants exhibited mild gingivitis, while 40% had moderate gingivitis. Spearman’s test demonstrated a strong and statistically significant correlation between motivation and gingivitis (ρ = 0.714; p = 0.001), indicating that higher motivation was associated with better gingival health. In conclusion, motivation plays a crucial role in shaping oral health behaviors during pregnancy and is significantly related to the incidence of gingivitis. Strengthening maternal motivation through targeted health education and integrated maternal–dental health programs is essential to reduce gingivitis risk and support optimal pregnancy outcomes.